The sources of quality in the pharmaceutical industry - Enrique A. Yacuzzi; Fernando Martín; Gabriel Vignola; Verónica Mayochi; Dante Tollio (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2004)
This paper analyzes the sources of quality of a pharmaceutical product. After identifying eight quality dimensions, a framework of hypothetical sources that contribute the most to shape those dimensions is established. The framework, based on Garvin's pioneering work, is applied to case studies of laboratories operating in Argentina. Framework relevance is considered using correlation analysis. Laboratories are ranked through expert opinion by the quality of its products using the eight dimensions mentioned above; it is observed that there is no perfect parallelism in ranking along all dimensions, possibly revealing different managerial priorities and uses of resources among laboratories, as well as different sources of quality and different business strategies. Correlation analysis also suggests that the study of a pharmaceutical product is a complex task when a modern concept of quality is considered. Once the existence of different quality dimensions is accepted, the following two questions are investigated: (1) Are there specific sources of quality that support some dimensions (and not others) and that are based on identifiable organizational aspects or specific technologies? (2) What are the generic sources of quality (affecting all dimensions) and in what way do they contribute to improve performance or highlight quality dimensions? It is assumed as a starting point that among the sources of quality there are generic sources, affecting all dimensions, and specific sources, which affect only some dimensions. In concrete cases, specific quality sources are identified, although the search for specific quality sources for each dimension is not conclusive. The study of generic quality sources, however, suggests that corporate systems, corporate culture, and management policies contribute to incorporate quality in a product. Thus quality results from the interaction between generic and specific sources. In the final part of the paper, recommendations for academics and industrialists are provided, as well as some conclusions.
Keywords: M10; M11; M14; 330; pharmaceutical product; Garvin's quality dimensions; quality sources; pharmaceutical laboratories in Argentina; corporate systems; corporate culture; Pharmazeutische Industrie; Pharmazeutisches Produkt; Produktqualität